Towards a Media-Archaeology of Sirenic Articulations Listening with Media-Archaeological Ears - Ernst, Wolfgang (The Nordic Journal of Aesthetics, 2016)
Media archaeology is not just a methodological claim but first of all a research practice of media culture. The case study described in this text is meant to demonstrate that archaeoacoustics can be applied to cultural aesthetics as well. The research expedition of April 2004 exploring the sonosphere of the Li Galli islands facing the Italian Amalfi coast measured the sonosphere of the acoustic theatre where the Homeric Sirens are supposed to have sung, resulting in surprising findings about the acoustic real(ity) lurking behind the myth. The relation between media archaeology and aesthetics is a dialectic one: Only through the application of most positivistic acoustic measurement technologies can new evidence against the philological tradition be gained, while at the same time these data only make aesthetic sense when coupled with cultural knowledge.